2020
DOI: 10.1021/acs.est.9b06643
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Atmospheric PM-Bound Reactive Oxygen Species, Their Half-Lives, and Regulated Pollutants: Investigation and Preliminary Model

Abstract: The concentration, nature, and persistence of particulate matter (PM)-bound reactive oxygen species (ROS) are of significant interest in understanding how atmospheric pollution affects health. However, the inherent difficulties in their measurement, particularly regarding the so-called "short-lived" ROS, have limited our understanding of their persistence and concentrations in the atmosphere. This paper aims to address this limitation through the analysis of PM-bound ROS measurements from the Particle Into Nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Fuller et al (2014) observed a decrease by about a factor of five in ROS content of laboratory generated oxidized organic aerosols within the first 15 minutes of their being capturing on PTFE filters. Recently, Brown et al (2020) estimated up to 71% short-lived (defined as having a half-live of 5 mins or less) ROS to total hourly averaged PM-bound ROS at a site in the in Heshan, China. Zhang et al (2022) showed that on average more than 90% of ROS in a photochemically aged mixture of primary combustion soot particles and naphthalene or β-pinene aerosols were short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…Fuller et al (2014) observed a decrease by about a factor of five in ROS content of laboratory generated oxidized organic aerosols within the first 15 minutes of their being capturing on PTFE filters. Recently, Brown et al (2020) estimated up to 71% short-lived (defined as having a half-live of 5 mins or less) ROS to total hourly averaged PM-bound ROS at a site in the in Heshan, China. Zhang et al (2022) showed that on average more than 90% of ROS in a photochemically aged mixture of primary combustion soot particles and naphthalene or β-pinene aerosols were short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows the correlation coe cient (r) between OPv (nmol min − 1 m − 3 ) and the trace gases (NO 2 , SO 2 , CO, O 3 ) (µg m − 3 ). Strong correlations (r 2 = 0.87) were observed with ozone during day-time, which functions both as an atmospheric oxidant and as a precursor to other important oxidants such as hydroxyl and nitrate radicals formed during photochemical processes and/or ozonolysis reactions (Brown et al 2020) and 60 µg m − 3 (NAAQS 2009)) to assess the toxicity of PM 2.5 . Figure 7 depicts the daily variance of the measured OPv and OPm, as well as the daily Hazard Index.…”
Section: Oxidative Potential (Op) Of Pm 25mentioning
confidence: 99%
“…It's worth noting that a strong association between CO and OPv (r 2 = 0.47) was also detected during the day. These ndings could indicate that high-level organics in both the gas and particle phases of vehicular emissions are responsible for the generation of PM-bound ROS, as organics are oxidised via hydroxyl radical-initiated processes(Brown et al 2020). Pearson's correlation coe cients were also calculated to nd associations between OP and speci c components in PM 2.5 that contributed to DTT.…”
mentioning
confidence: 99%
“…5 -bound ROS radicals, which can effectively trap radicals and can be used to study the relationship between PM 2 . 5 and the growth of ROS radicals [ 5 ]. Zhou J et al [ 6 ] measured ROS using 2,7-dichlorofluorescein diacetate (DCFH-DA) combined with a horseradish peroxide (HRP) catalyst.…”
Section: Introductionmentioning
confidence: 99%